Neutropenia, neutrophilia, and neutrophil–lymphocyte ratio as prognostic markers in patients with metastatic castration-resistant prostate cancer. (May 2022) - Meisel, Alexander; de Wit, Ronald; Oudard, Stephane; Sartor, Oliver; Stenner-Liewen, Frank; Shun, Zhenming; Foster, Meredith; Ozatilgan, Ayse; Eisenberger, Mario; de Bono, Johann S.
Background and purpose: Chemotherapy-induced neutropenia and neutrophil-to-lymphocyte ratio (NLR) are potentially useful prognostic markers in patients with metastatic castration-resistant prostate cancer (mCRPC). This post hoc analysis investigated whether these markers can be utilized for dose considerations and evaluated the prognostic impact of leukocyte subtypes. Patients and methods: PROSELICA assessed the non-inferiority of cabazitaxel 20 mg/m 2 (C20; n  = 598) versus 25 mg/m 2 (C25; n  = 602) for overall survival (OS) in patients with mCRPC previously treated with docetaxel. The association of grade ⩾ 3 neutropenia, NLR, baseline neutrophilia and lymphopenia with OS, progression-free survival (PFS), and prostate-specific antigen response rate (PSArr) was investigated by an unplanned uni- and multivariate analyses. Results: PROSELICA confirmed the negative prognostic value of increased baseline NLR [⩾3, hazard ratio (HR) 1.40; p  < 0.0001], but did not identify a subgroup of patients benefiting more from C20 or C25. In this post hoc analysis, patients who developed grade ⩾3 neutropenia ( n  = 673) had a significantly improved OS [∆OS = 2.7 months, HR = 0.78 (95% CI 0.68–0.89)] with the greatest advantage observed in patients with baseline neutrophilia [ n  = 85; 5.3 months, 0.60 (0.42–0.84)]. After adjustment for the Halabi criteria, neutropenia grade ⩾ 3 was the only biomarker that remained significantly associated with OS [ (HR 0.86 (0.75–0.98)], PFS [HR 0.78 (0.68–0.88)], and PSArr [odds ratio (OR) 1.82 (1.37–2.41)] while neutrophilia showed the strongest association with OS [1.53 (1.29–1.81)]. Conclusions: Grade ⩾ 3 neutropenia was the only leukocyte-based biomarker associated with all key outcome parameters in mCRPC patients receiving cabazitaxel and might be able to overcome the negative prognostic effect of baseline neutrophilia. NCT number: NCT01308580